MOF-templated nanorice–nanosheet core–satellite iron dichalcogenides by heterogeneous sulfuration for high-performance lithium ion batteries. Issue 48 (29th November 2016) - Pang, Huicong; Sun, Weiwei; Lv, Li-Ping; Jin, Feiying; Wang, Yong
Abstract : The nanorice–nanosheet core–satellite structure of FeS2 synthesized by heterogeneous sulfuration from a MIL-88-Fe precursor achieves highly reversible larger-than-theoretical Li-storage capacities. Abstract : Metal dichalcogenides are promising electrode materials for lithium-ion batteries (LIBs) because of their large specific capacities. Their electrochemical properties are largely dependent on their composition, morphology and porosity. This paper reports a metal–organic framework (MOF) synthetic approach for achieving a nanorice–nanosheet core–satellite structure of sulfur-doped porous carbon coated FeS2 (FeS2 @S-C NR-NS (MOF)). Unlike substantial morphology transformation in the sulfuration process from common Fe-based precursors, the nanorice skeleton can be inherited from the Fe-MOF precursor, while small nanosheets are formed on the exterior surface due to heterogeneous sulfuration. When evaluated as the anode material for LIBs, FeS2 @S-C NR-NS (MOF) exhibits excellent cycling performances with a larger-than-theoretical reversible capacity of 1336.5 mA h g −1 after 200 cycles at 100 mA g −1 and good high-rate capability. The improved structural stability, electrical conductivity and enhanced kinetic rate of ions and electrons have been attributed to the hierarchical structure, porous characteristics, and S-doped carbon overlayer in the electrode.